Tracking Openness and Topic Evolution of COVID-19 Publications January 2020-March 2021: Comprehensive Bibliometric and Topic Modeling Analysis - Maider San Torcuato; Núria Bautista-Puig; Olatz Arrizabalaga; Eva Méndez (JMIR Publications, 2022)
BackgroundThe COVID-19 outbreak highlighted the importance of rapid access to research. ObjectiveThe aim of this study was to investigate research communication related to COVID-19, the level of openness of papers, and the main topics of research into this disease. MethodsOpen access (OA) uptake (typologies, license use) and the topic evolution of publications were analyzed from the start of the pandemic (January 1, 2020) until the end of a year of widespread lockdown (March 1, 2021). ResultsThe sample included 95,605 publications; 94.1% were published in an OA form, 44% of which were published as Bronze OA. Among these OA publications, 42% do not have a license, which can limit the number of citations and thus the impact. Using a topic modeling approach, we found that articles in Hybrid and Green OA publications are more focused on patients and their effects, whereas the strategy to combat the pandemic adopted by different countries was the main topic of articles selecting publication via the Gold OA route. ConclusionsAlthough OA scientific production has increased, some weaknesses in OA practice, such as lack of licensing or under-researched topics, still hold back its effective use for further research.